Correlates of Academic Procastination and Academic Achievement of Undergraduate Students - Gartia, Radhakanta; Sharma, Sushama; Sood, Ramana (JOURNAL OF INDIAN EDUCATION, 2011)
Procrastination is now a common phenomenon among students particularly those at the higher level and this is doing more harm to their academic achievement than good.Therefore, the present study was conducted to examine the relationship between academic procrastination and academic achievement of undergraduate students. The study was conducted on a total sample of 90 undergraduate students of Sambalpur, University of Odisha. The adapted version of Tuckman Procrastination Scale (adapted by the investigators) was used for the collection of data. Findings indicated that; a significant correlation was found between academic procrastination and academic achievement of undergraduate students, significant difference also exists in the academic achievement of students having low, moderate and high academic procrastination. Students with low procrastination performed better than the students having moderate and high procrastination. Results further revealed that the subjects procrastinate in the same way irrespective of their gender. Implications of procrastination on academic achievement of students were suggested.